Community-Based Natural Disaster Mitigation Participation Model in Majene Regency - Tamrin, Saddam Husain; Syahrinullah, Syahrinullah; Pauzi, Rizal; Asratillah, Muh; Rukmana, Novayanti Sopia (PINISI Discretion Review, 2025)
This study proposes a community-based disaster mitigation model to enhance public participation in disaster risk reduction efforts in Majene Regency, Indonesia. The regency is highly vulnerable to natural hazards such as floods, landslides, earthquakes, and fires. The research aims to examine the current state of community participation in disaster mitigation and identify factors that hinder or support public involvement. The study employs a qualitative approach, focusing on the perceptions, motivations, and actions of research subjects within their natural context. Data is collected through observation, interviews, focus group discussions, and documentation, with validity ensured through triangulation. The proposed model consists of eight stages: (1) Training of Trainers for Regency-level Facilitators, (2) Training of Trainers for Village/Sub-district Facilitators, (3) Formation of Disaster Mitigation Communities, (4) Building community cohesiveness, (5) Participatory risk assessment, (6) Participatory action planning, (7) Program implementation, and (8) Participatory evaluation. The model emphasizes the central role of the community in all stages of disaster mitigation. It seeks to empower local communities to leverage their resources and knowledge in reducing risks. The study provides recommendations for strengthening participation, including reinforcing regulations, initiating pilot projects, allocating budget for infrastructure, and building local leaders' capacity. By adopting a community-centric approach, the model aims to cultivate a culture of disaster awareness and resilience in Majene Regency. It seeks to empower communities to become active agents in risk reduction, ultimately contributing to a safer and more sustainable future.